2017
DOI: 10.3201/eid2303.161553
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Transmission ofmcr-1Colistin Resistance Gene from Small-Scale Poultry Farms, Vietnam

Abstract: We investigated the consequences of colistin use in backyard chicken farms in Vietnam by examining the prevalence of mcr-1 in fecal samples from chickens and humans. Detection of mcr-1–carrying bacteria in chicken samples was associated with colistin use and detection in human samples with exposure to mcr-1–positive chickens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 12 publications
5
99
1
1
Order By: Relevance
“…(2016a) . A recent farm‐based study in Vietnam of the colistin resistance gene mcr‐1 in E. coli showed that detection of mcr‐1 in humans was associated with exposure to mcr‐1 ‐positive chickens .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2016a) . A recent farm‐based study in Vietnam of the colistin resistance gene mcr‐1 in E. coli showed that detection of mcr‐1 in humans was associated with exposure to mcr‐1 ‐positive chickens .…”
Section: Resultsmentioning
confidence: 99%
“…Adding colistin to feed or water is worrisome as such selective pressure will lead to resistance in pigs as documented by Nguyen et al (2016a) [10]. A recent farm-based study in Vietnam of the colistin resistance gene mcr-1 in E. coli showed that detection of mcr-1 in humans was associated with exposure to mcr-1-positive chickens [28].…”
Section: Resultsmentioning
confidence: 99%
“…While the former is suggestive of recent inter-host transmission or common acquisition from common sources, the second can be the basis to study microbial evolution or diversification as a consequence of host speciation, especially if phylogenies can be dated using ancient microbiome samples [71] or other time constraints [72]. Our framework can thus be exploited to study inter-host species and zoonotic microbial transmission that is currently mostly limited to specific pathogens of interest [73][74][75][76][77][78]. The catalog of primate-associated microbial genomes can thus serve as a basis for a better comprehension of the human microbiome in light of recent and ancient cross-primate transmission and environmental acquisition of microbial diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to colistin is particularly worrisome as colistin can be the last available treatment for CPE/K (Falagas, Karageorgopoulos, & Nordmann, ). A study on backyard chicken farms in Vietnam concluded that detection of mcr‐1 ‐carrying bacteria in chicken samples was associated with colistin use and that detection in human samples was associated with exposure to mcr‐1 ‐positive chickens (Trung et al, ). Through interviewing pig farmers in Cambodia, Ström, Boqvist, et al ()) found that antibiotic use, including colistin, was common in pig farms and sometimes used as prophylactic treatment.…”
Section: Discussionmentioning
confidence: 99%